Elaboración del manual para la implementación del sistema administrativo y financiero de gestión de proyectos del Centro de Investigación en Enfermedades Infecciosas (CIEI) de la Pontificia Universidad Católica del Ecuador (PUCE) sede Quito - Aristizabal Herrera, Christian Adrian (2015)
Project management is the administration tool that its purpose is reaching their goals across of resources planning in certain times. Its good direction is based in the standards and they’re determinate in the PMBOOK because if we stablish definitions and basic standards that contributed to maintained the relationships between costs, time, and reach of the project. It’s important that the Enterprise manages projects that they have with their own systems, and their essences will be administration based of in fulfillment establish standards. To make this work the information has been divided in four chapters distributed of the next way: In the first chapter it is establish all the ideas about the Project Management and system information with the goal to establish the model, phases and rules of PMBOOK. It is going to be implemented in the model. In the chapter two it is general way of the situation that it’s showing in the CIEI nowadays In the chapter three it’s making the analysis FODA of CIEI, and also it’s making of the handbook of proposed procedures based in the standards of Project Management. This chapter includes the processes map design of job profile, policies, procedures, formats, and flowcharts for each process. In the last section it’s the conclusions and recommendations of the thesis. The objective this work is that the Centro de Investigación de Enfermedades Infecciosas CIEI proceed with the implementation of the proposed handbook.